MOBLOCKS tangible user interface (TUI) for mobile robot control as an educational tool for preschoolers - Caranguian, Luther Paul D. R.
The Moblocks project aims to develop an embedded system for mobile robot (mobot) control based on tangible user interface (TUI). TUI is a new research area that aims to provide better systems for human-computer interaction. It has been found that the use of tangible interfaces is ideal for young children. The tangible nature of the system coupled with conventional sound and visual effects offer adequate sensory stimulation that is lacking in traditional computer interfaces. The Moblocks system is composed of a mobot, wooden blocks, a tray and a play area. The blocks represent the instructions to the robot. The tray has slots for four blocks and sensors to detect the sequence of blocks. The instructions are sent to the mobot via a wireless link. Several implementations of the system were developed and compared. Color sensors and the mutual inductance technique were implemented and tested for their effectiveness as block detectors. Stepper motors and DC motors with feedback were implemented and tested for precision. Precision is important because the mobot's movements should match the dimensions of the play area. Radio Frequency (RF) link and Infrared (IR) link were implemented and tested for their reliability for wireless transmission. Moblocks aims to be an effective learning tool for preschoolers by being easy to play, engaging, and fun.